THE INTEGRATED THEORY OF SOCIOPRENEURIAL BEHAVIOUR: SOCIOPRENEURIAL BEHAVIOUR FORMATION AND IMPACT - Sidek, Shafie; Arrasyid, Muhammad Iqbal (Jurnal 'Ulwan, 2022)
Social entrepreneurs focus on gaining social benefits rather than maximization of business profit. A number of theories and models have been proposed by prior researchers to expound on sociopreneurial behaviour. This article aims to integrate the existing theories and those models into an Integrated Theory of Sociopreneurial Behaviour, which combines both formation and impact of sociopreneurial behaviour. The theory states that, firstly, external support(s) and/or hindrance(s) are significant moderator(s) to strengthen or weaken the prediction of sociopreneurial intention conversion into successful sociopreneurial behaviour. Secondly, the sociopreneurial behaviour should foster direct and/or indirect improvement to both the community and the sociopreneur without conflict of interest. This article discusses the literature support and proposes future research approaches.